Analisis Faktor-Faktor Yang Mendorong Pembelian Impulsif Online Pada Aplikasi TikTok - Oktaviana, Bella; Astuti, Budi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study aims to explain the factors that encourage online impulse purchases on the TikTok Shop application. The study population consists of all Indonesian people who have made online purchases through the TikTok Shop. In this study, researchers used convinience sampling with a total sample of 138 respondents obtained through an online Google Forms survey. The results of this study indicate that 1) there is a positive effect of the hedonic browsing variable on urge to buy impulsively, 2) there is an indirect effect between utilitarian browsing and the urge to buy impulsively through the influence of hedonic browsing, 3) the interpersonal influence variable has a negative effect on both hedonic and utilitarian browsing, 4) there is a positive effect of the visual appeal variable on hedonic browsing, but it has a negative effect on utilitarian browsing, 5) the portability variable does not have a positive effect on hedonic browsing, but it has a positive effect on utilitarian browsing, 6 ) the quality of information variable has a negative effect on the hedonic browsing experience in the TikTok Shop, but it has a positive effect on the utilitarian browsing experience in the TikTok Shop